The need for greater transparency in the moderation of borderline terrorist and violent extremist content - Ellie Rogers (Internet Policy Review, 2025)
Content moderation is becoming an increasingly prominent feature of legislation to increase the safety of online spaces. One aspect of this debate is moderating borderline content in the context of terrorism and violent extremism (borderline TVEC). For content moderation approaches to be proportionate in respecting users’ rights whilst improving the safety of online spaces, transparency is crucial. This importance is recognised within recent legislation such as the Digital Services Act and the Online Safety Act. However, legislation does not provide direct requirements for transparency surrounding the moderation of borderline TVEC. As a result, there are concerns that transparency reporting will continue to focus on removals of content that is illegal or violative in nature. This article argues that there needs to be more transparency surrounding the moderation of borderline TVEC. Through a review of the literature, this article discusses the importance of increased transparency surrounding the moderation of borderline TVEC, and demonstrates the ways in which current legislation, tech company policies and content moderation processes are not conforming to transparent practices in the context of borderline TVEC moderation.